HUBUNGAN ANTARA MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA GURU: SMKN 1 SUBOH SITUBONDO - AHMAD MAULIDI MARFIANTO (Dewan Pendidikan Bondowoso, 2023)
This study aimed to determine the relationship between motivation and organizational climate on teacher performance at SMK 1 Suboh Situbondo. This study used a quantitative approach to the type of correlational research. The study population was all teachers from SMK Negeri 1 Suboh Situbondo which consisted of 100 research samples selected by proportional random sampling technique. The technique used in collecting data was using a questionnaire via Google Form, the questionnaire consists of 3 parts, namely: contains motivation, organizational climate and teacher performance. All tests in this study used the SPSS application. The results of this study can be concluded that Between Teacher Motivation and Performance there is a weak relationship, then Between Organizational Climate and Teacher Performance there is a strong relationship then If the organizational climate is good, then Teacher performance is also good. And conversely, if the organizational climate is bad, then the teacher's performance is also bad.